OPTIMALISASI ELEKTONIK MEDICAL RECORD (EMR) PADA LAYANAN KESEHATAN DI TINGKAT PRIMER PUSKESMAS BOTANIA KOTA BATAM - Situmorang, Masriani; Mulyana; Rahmawati (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
The Batam City Health Office facilitates health centers in its working area by using the health center information system to improve the effectiveness and efficiency of patient services. Assistance in the implementation of information systems related to electronic medical records is needed in puskesmas so that the use of information systems can be optimized. This activity aims to improve officer performance in processing electronic medical record data on information systems. This service activity was carried out at the Botania Health Center, Batam City. The methods used in this activity include counseling on optimizing the puskesmas information system, especially electronic medical records, as well as question and answer sessions. Overall, this community service activity went well. Participants also showed good enthusiasm, which was seen from the beginning of the activity to the end of the community service activity. The organizing team provided material related to optimizing the use of the puskesmas information system as well as system maintenance that can be carried out by puskesmas officers themselves without having to rely on the technical team from the Health Office. Socialization and training activities on the use of information systems have been successfully carried out at Puskesmas Botania. Technical solutions related to the use of the ePuskesmas application have been provided, including suggestions for the future development of the puskesmas management information system.